Caracterização química e palinológica da própolis produzida no litoral norte do estado da Bahia - Matos, Vanessa Ribeiro (2012)
Total phenolic content from nineteen propolis samples produced in the Northern Coastal region of Bahia State was assessed. The samples were diluted and analyzed using the Folin-Ciocalteau method. Readings were performed at a wavelength of 740 nm. Next, these measurements were used to estimate the average content of total phenols in gallic acid equivalence, by the calibration curve’s equation (C=87.95+0.585x). The municipality of Inhambupe displayed the highest (36.78±1,52 mg GAE/g) and lowest (7.68±2,58 mg GAE/g) values of phenol content among the samples analyzed. The results demonstrate that Bahia’s propolis comply with the requirements of the Brazilian legislation. The values obtained are lesser to those found in other propolis samples in Brazil.